Optimization of banks' value: Practical challenges - Jan Koleśnik; Jacek Nadolski (Journal of Banking and Financial Economics (JBFE), 2023)
The aim of the article is to verify the conceptual model of integrated optimization of a bank's value, which enables the integration of the risk management process with business processes while maintaining compromise between the safety (stability) of a bank's operations and striving to maximize its value. The model is an attempt at a comprehensive solution to such dilemmas as shaping a bank's value ex ante, not ex post. Verifi cation of the model has shown that the model works in accordance with the adopted assumptions and leads to the achievement of the basic goal for which it was constructed. In practice, it means the possibility of ensuring a compromise between the safety and effectiveness of a bank's operations, which, in the context of ongoing changes in its environment, allows for a long-term competitive advantage.
Keywords: C61; G21; G32; 330; Bank management model; Integrated value optimization; Stochastic simulations; Decision support systems